Integrative taxonomy describes a new species of the genus Sinocyclocheilus (Cypriniformes, Cyprinidae) from the Beipanjiang River, Guizhou Province, southwest China - Zhi-Xia Chen; Tao Luo; Zi-Fa Zhao; Ming-Yuan Xiao; Jia-Jun Zhou; Jiang Zhou (Zoosystematics and Evolution)
We describe a new species, Sinocyclocheilus panzhouensis sp. nov., from Panzhou City, Guizhou Province, China, using morphological and genetic evidence. Phylogenetic analysis of mitochondrial cytochrome b (Cyt b) and NADH dehydrogenase subunit 4 (ND4) sequences reveals distinct genetic divergence from related species, with genetic distances ranging from 1.7–14.2% in Cyt b and 1.2–12.6% in ND4. Morphologically, S. panzhouensis sp. nov. is characterised by absence of a horn-like structure and indistinct elevation at the head-dorsal junction; body covered with tiny scales, with irregular black markings; wide mouth, 7.8–9.3% of standard length and longer pectoral fin 17.9–30.6% of standard length; last unbranched ray of dorsal-fin with weak serrations along posterior margin; tip of pectoral fins not reaching the pelvic-fin origin; lateral line complete and curved, with pores 71–79; and eight rakers on the first gill arch. This discovery raises the number of Sinocyclocheilus species in Guizhou to 19, with five species found in the Beipanjiang River. This study highlights the need for further surveys in Guizhou to explore the full species diversity of the genus.